The effect social information processing in six-year-old children has on their social competence and peer relationships - Ogelman, H. G.; Seven, S. (My University, 2012)
The purpose of this study was to investigate the effect social information processing levels has on the social competence (entering a peer group, response towards provocation, response to failure, response to success, social expectations, teacher expectations, reactive aggression, proactive aggression) and peer relationship (prosocial behaviour, exclusion, victimisation) variables of six-year-old children. The Social Information Processing Evaluation, The Preschool Taxonomy of Problem Situation, The Child Behavior Scale, and Peer Victimization Scale were used in this study. According to the study results, it is obvious that skills within the social information processing model of six-year-old children have an effect on their social competence and peer relationship variables. © 2012 Copyright Taylor and Francis Group, LLC.
Keywords: peer relationships; six-year-old children; social competence; social information processing